PERBANDINGAN METODE CERAMAH DAN HEALTH COACHING TENTANG BASIC LIFE SUPPORT (BLS) UNTUK REMAJA MASJID - Ronal Surya Aditya (Jurnal Keperawatan, 2019)
Basic life support (basic life support) is an action when a patient is found to be suddenly immobile, unconscious, or not breathing, so check the patient's response. The purpose of this study was to determine the effectiveness of the lecture method and health coaching about BLS (Basic Life Support) in mosque youth. The research design is quasy-experiment. The population of this study was all male mosques in the year totaling 80 people. The sample in this study was simple random sampling. The research instrument used is the Heart-saver® observation sheet. The results showed differences in the results of Wilcoxon and Mann-Whitney analysis in the treatment and control groups. For the control group, the lecture produced Wilcoxon (p = 0.26) and Mann-Whitney significance (p = 0.32). Whereas in the treatment group that received Health coaching produced Wilcoxon significance (p = 0.001) and Mann-Whitney (p = 0,000). Conclusion: Health coaching is more effective than the lecture method. Suggestion: the next researcher will combine health coaching with other methods to be able to provide more effective knowledge and skills.